Ecuador y Marruecos: perspectivas para una relación integral - Núñez Jaramillo, Magdalena María (2015)
Ecuador's Foreign Policy was traditionally focused on resolving the border dispute with Peru, the relationship with the United States and, subsequently, on the security issues of the border with Colombia. This situation constrained the possibility to explore the benefits of a deeper relationship with other world regions. The current Foreign Policy of Ecuador seeks to promote relations with all countries of the world. This research outlines a proposal of strategic objectives and guidelines of Foreign Policy of Ecuador and Morocco, based on the strategic importance of Morocco for the world. The main objective is to identify the opportunities that this relationship could offer for the fulfillment of the development objectives of Ecuador. The analysis and method used are nourished by the principles of the main theories of international relations, particularly the contributions of Constructivism. Consequently, speeches, ideas and perceptions are key elements of the study. Morocco is considered a country with a dynamic economy that enjoys a strategic geographical location. It has showed a significant growth in recent years, although certain social problems remain. The Moroccan government has launched initiatives to promote the country's development in various areas (industry, agriculture, fisheries, energy). Moroccan Foreign Policy covers neorealist elements ("sovereignty" and territorial "integrity" associated with the problem in Western Sahara), neoliberal (human development, cooperation and participation in multilateral forums) and constructivist (importance of "culture" and "values” and promoting its “image” internationally). Ecuador and Morocco share similar visions in various fields such as UN reform, migration and refugees, Food Sovereignty, South-South Cooperation, Climate Change and the improvement of the energy matrix. Both countries should take advantage of the cultural similarities as a mechanism to promote closer ties between them. Meanwhile, the conflict in the Sahara and the fight against terrorism are sensitive areas of the bilateral relationship.